Influence of Preoperative Sagittal Alignment on Functional Recovery in Operated Cases of Cervical Spondylotic Myelopathy - Acharya, Shankar; Khanna, Varun; Kalra, Kashmiri Lal; Chahal, Rupinder Singh (Asian journal of neurosurgery, 2023)
Objective We examine the influence of preoperative cervical sagittal curvature (lordotic or nonlordotic) on the functional recovery of surgically managed cases of cervical spondylotic myelopathy (CSM). The impact of sagittal alignment on the functional improvement of operated CSM cases has not been thoroughly investigated. Materials and Methods We did retrospective analysis of consecutively operated cases of CSM from March 2019 to April 2021. Patients were grouped into two categories: lordotic curvature (with Cobb angle > 10 degrees) and nonlordotic curvature (including neutral [Cobb angle 0–10 degrees] and kyphotic [Cobb angle < 0 degrees]). Demographic data, and preoperative and postoperative functional outcome scores (modified Japanese Orthopaedic Association [mJOA] and Nurick grade) were analyzed for dependency on preoperative curvature, and correlations between outcomes and sagittal parameters were assessed. Results In the analysis of 124 cases, 63.1% (78 cases) were lordotic (mean Cobb angle of 23.57 ± 9.1 degrees; 11–50 degrees) and 36.9% (46 cases) were nonlordotic (mean Cobb angle of 0.89 ± 6.5 degrees; –11 to 10 degrees), 32 cases (24.6%) had neutral alignment, and 14 cases (12.3%) had kyphotic alignment. At the final follow-up, the mean change in mJOA score, Nurick grade, and functional recovery rate (mJOArr) were not significantly different between the lordotic and nonlordotic group. In the nonlordotic group, cases with anterior surgery had a significantly better mJOArr than those with posterior surgery (p = 0.04), whereas there was similar improvement with either approach in lordotic cases. In the nonlordotic group, patients who gained lordosis (78.1%) had better recovery rates than those who had lost lordosis (21.9%). However, this difference was not statistically significant. Conclusion We report noninferiority of the functional outcome in the cases with preoperative nonlordotic alignment when compared with those with lordotic alignment. Further, nonlordotic patients who were approached anteriorly fared better than those approached posteriorly. Although increasing sagittal imbalance in nonlordotic spines portend toward higher preoperative disability, gain in lordosis in such cases may improve results. We recommend further studies with larger nonlordotic subjects to elucidate the impact of sagittal alignment on functional outcome.